FOXM1: An emerging master regulator of DNA damage response and genotoxic agent resistance - Stefania Zona; Laura Bella; Matthew J. Burton; Gabriela Nestal de Moraes; Eric W.‐F. Lam (2014)
FOXM1 is a transcription factor required for a wide spectrum of essential biological functions, including DNA damage repair, cell proliferation, cell cycle progression, cell renewal, cell differentiation and tissue homeostasis. Recent evidence suggests that FOXM1 also has a role in many aspects of the DNA damage response. Accordingly, FOXM1 drives the transcription of genes for DNA damage sensors, mediators, signal transducers and effectors. As a result of these functions, it plays an integral part in maintaining the integrity of the genome and so is key to the propagation of accurate genetic information to the next generation. Preserving the genetic code is a vital means of suppressing cancer and other genetic diseases. Conversely, FOXM1 is also a potent oncogenic factor that is essential for cancer initiation, progression and drug resistance. An enhanced FOXM1 DNA damage repair gene expression network can confer resistance to genotoxic agents. Developing a thorough understanding of the regulation and function of FOXM1 in DNA damage response will improve the diagnosis and treatment of diseases including cancer, neurodegenerative conditions and immunodeficiency disorders. It will also benefit cancer patients with acquired genotoxic agent resistance.